Shoe Dog: A Memoir by the Creator of Nike - Harvey, Patrick J. (The Accounting Review, 2017)
Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Share Icon Share Facebook Twitter LinkedIn MailTo Tools Icon Tools Get Permissions Search Site Cite View This Citation Add to Citation Manager Citation Patrick J. Harvey; Shoe Dog: A Memoir by the Creator of Nike. The Accounting Review 1 July 2017; 92 (4): 269–272. https://doi.org/10.2308/accr-10538 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentThe Accounting Review Search Advanced Search